Analisis Faktor Penghambat Guru dalam Pembelajaran Tematik di SD/MI - Nafizaturrrahmi Nafizaturrrahmi; Shindy Lestari; Mohammad Agung Rokhimawan (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The research carried out aims to determine the inhibiting factors of teachers in thematic learning in elementary school. This type of research uses a qualitative approach with descriptive methods. The data collection technique used is a literature study. The result of the research analysis shows that at the planning stage teachers have difficulty in preparing syllabi and lesson plans according to the conditions and environment of students, teachers also find it difficult to prepare appropriate learning media in thematic learning. Meanwhile, at the implementation stage, the teacher had difficulty in adjusting the time allocation with learning and the demands of completing one learning in one meeting, this had an impact on the basic competency adjustment with learning material in half a day, it was difficult to synergize the delivery of objectives and apply a scientific approach to learning. So as to better understand the concepts and implementation of thematic learning.